Leading Difficult Conversations Series #4: Communication Styles under Stress - Christy Chiarelli (EDIS)
This new 3-page publication of the UF/IFAS Department of Agricultural Education and Communication focuses on helping leaders better understand their communication style when under stress. Even with adequate preparation, difficult conversations can still be stressful. By understanding their communication style under stress, leaders can better regulate their personal responses to ensure a productive conversation. Written by Christy C. Chiarelli. https://edis.ifas.ufl.edu/wc404